Evolution of Simulation-Driven Science Education: Three Decades of Scholarly Patterns and Research Dynamics (1996–2025) - Suyidno Suyidno; Misbah Misbah; Mastuang Mastuang; Laili Komariyah; Qamariah Qamariah; Mohd Zaidi Bin Amiruddin; Nor Farahwahidah Abdul Rahman (CV FOUNDAE, 2026)
This study maps the global landscape of simulation-based science education (SBSE) research to identify publication trends, influential contributors, collaboration patterns, and future research opportunities. A bibliometric analysis was conducted on 4,489 Scopus-indexed publications published between 1996 and August 25, 2025, using VOSviewer and Biblioshiny; therefore, 2025 should be interpreted as a partial year. The results indicate sustained growth in the literature, with a marked increase during 2020–2024 that may be associated with the expansion of virtual and augmented reality (VR/AR), online learning, and post-pandemic pedagogical adaptation. Keyword evolution suggests a shift from conventional computer-based simulation toward more immersive and data-informed approaches, including machine learning, learning analytics, and adaptive learning systems. The United States and China produced the largest publication outputs, while Indonesia recorded the highest proportion of international collaboration among the top 10 most productive countries (29%). Overall, the findings highlight the growing importance of cross-border collaboration, sound instructional design, and the ethical integration of intelligent technologies in advancing SBSE research and supporting more inclusive and adaptive science learning environments